2015
DOI: 10.1177/1091581815607068
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation of Talc Induces Infiltration of Macrophages and Upregulation of Manganese Superoxide Dismutase in Rats

Abstract: Talc is a mineral that is widely used in cosmetic products, antiseptics, paints, and rubber manufacturing. Although the toxicological effects of talc have been studied extensively, until now no detailed inhalation study of talc focusing on oxidative stress has been done. This repeated 4 weeks whole-body inhalation toxicity study of talc involved Sprague-Dawley rats. Male and female groups of rats were exposed to inhaled talc at 0, 5, 50, and 100 mg/m(3) for 6 hours daily, 5 days/week for 4 weeks. The objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Similar findings were reported in rats exposed to non-asbestiform talcum powder for 6 h per day for 4 weeks via whole-body inhalation ( 28 ). The authors observed increases in macrophage infiltration at 50 and 100 mg/m 3 talc, but not at the lowest concentration of 5 mg/m 3 .…”
Section: Resultssupporting
confidence: 87%
“…Similar findings were reported in rats exposed to non-asbestiform talcum powder for 6 h per day for 4 weeks via whole-body inhalation ( 28 ). The authors observed increases in macrophage infiltration at 50 and 100 mg/m 3 talc, but not at the lowest concentration of 5 mg/m 3 .…”
Section: Resultssupporting
confidence: 87%
“…Oxidative stress is induced when excessive ROS overwhelm the antioxidant defense system. This system is composed of non-enzymatic antioxidants such as ascorbic acid (vitamin C), alpha-tocopherol (vitamin E) and GSH, and enzymatic antioxidants such as superoxide dismutase, catalase and glutathione peroxidase (Birben et al, 2012;Shim et al, 2015;Valko et al, 2015). GSH is an important intracellular antioxidant that scavenges ROS, thus preventing inflammation and cell damage (Chaufan et al, 2014;Tajima et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The NR8383 cell line was chosen for this study as it provides a homogenous source of highly responsive alveolar macrophages ( 11 , 12 ). Moreover, it is an established and well characterized alveolar macrophage cell line with appropriate culture characteristics and suitable as comparator cell line for in vivo alveolar macrophage responses observed in the Sprague-Dawley rat model ( 11 , 12 ). The cell line was obtained from LGC Standards (cat#AgC11x3A, Teddington, Middlesex, UK) and used between passage numbers 2 and 20 from purchase.…”
Section: Methodsmentioning
confidence: 99%